Regulatory focus and junk food avoidance: The influence of health consciousness, perceived risk and message framing - Shimul, Anwar Sadat; Cheah, Isaac; Lou, Andrew Jerr (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
The purpose of this research is to examine: (1) the health-related factors namely perceived health consciousness and perceived risk that motivate a person's intention to avoid junk food consumption, and (2) the influence of regulatory focus (promotion vs prevention foci) on a person's intention to avoid junk food consumption under the conditions of gain-framing vs loss-framing health communication and messages. A set of hypotheses are tested across three studies. Study 1 (n = 148) shows that regulatory focus influences the consumers' intention to avoid junk food. Also, health consciousness mediates the relationship between regulatory focus and junk food avoidance intention. Study 2 (n = 132) finds that perceived risk amplifies the relationship between regulatory focus and health consciousness. Study 3 (n = 168) demonstrates that message framing combined with the appropriate regulatory focus positively influences the consumers' intention to avoid junk food. The findings validate and extend the current theoretical framework in relation to unhealthy eating behaviours (e.g., junk food consumption). Based on the findings of this research, the practitioners can utilise the correct type of health information or claims for the appropriate consumer segment (whether prevention or promotion foci) to effectively implement campaigns and programs.